β-defensin-4 as an endogenous biomarker in cows with mastitis - Neumann, Stephan; Siegert, Stephan; Fischer, Anneke (Frontiers in Veterinary Science, 2023)
Introduction Defensins are peptides with antimicrobial and immunomodulatory effects. Their concentration could be altered during infections and thus provide information on the prognosis and course of the disease. The aim of the present study was to investigate the defensin concentration in cows with mastitis in order to find correlations between clinical expression and course of the disease and the defensin concentration in milk and blood. Methods A total of 85 dairy cows were examined. Of these, 30 animals suffered from acute clinical mastitis, 25 animals were diagnosed with subclinical mastitis and 30 animals were considered a healthy comparison group. Beta-Defensin-4 (DEFB-4) was determined by a species-specific enzyme-linked immunosorbent assay (ELISA) (Bovine Defensin Beta 4 ELISA Kit, MyBioSource). Results The highest concentrations of DEFB-4 were detected in the animals with acute clinical mastitis. Values of 0 to 895 pg/mL (median: 115 pg/mL) were measured in milk and 40–1,016 pg/mL (median: 245 pg/mL) in serum. The concentrations of this group differed significantly from those of the animals with subclinical mastitis (p < 0.0001 serum; p = 0.015 milk). In this group, concentrations of 15–211 pg/mL (median: 46 pg/mL) were recorded in milk and 20-271 pg/mL (median: 85 pg/mL) in serum. Discussion Our results also show that in cases of acute mastitis after 12 days of treatment there is still an active inflammatory process in the tissue, because no significant reduction of somatic cells and defensin could be found after re-examination. Since the DEFB-4 concentrations of animals with clinical mastitis that had to be treated with antibiotics differed significantly from those of animals with subclinical mastitis that did not require antibiotic treatment, it can be assumed that bovine DEFB-4 is an important endogenous parameter for the defense against bacterial infections of the udder.